2013
DOI: 10.15177/seefor.13-01
|View full text |Cite
|
Sign up to set email alerts
|

Lead Tolerance and Accumulation in White Poplar Cultivated In Vitro

Abstract: Background and purpose: This paper analyses the lead tolerance and accumulation in white poplar genotypes in vitro, in order to optimize genotype evaluation and other procedures in their implementation in phytoremediation projects and landscaping in areas endangered by lead accumulation. Material and Methods: The lead tolerance and accumulation of five white poplar genotypes after 35 days in vitro cultivation on media supplemented with lead was examined. The following Pb(NO 3) 2 concentrations were used: 0, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
3
8
3
Order By: Relevance
“…In concordance with the results from some previous works (Kališova-Špirochova et al 2003, Katanić et al 2007, di Lonardo et al 2011, Kovačević et al 2013a, in most of the examined media no signs of intoxication were found on shoots. In this work, only sporadic necrotic changes were found on the roots formed in medium with 10 -3 M Pb(NO 3 ) 2 , which is consistent with the results by Kovačević et al (2013a) on the same medium. However, Bojarczuk (2004) reported an inhibitory effect of the medium with pH 5.5 and 2.0 mM Pb(NO 3 ) 2 on shoot and root development of calli of hybrid aspen on regeneration medium.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In concordance with the results from some previous works (Kališova-Špirochova et al 2003, Katanić et al 2007, di Lonardo et al 2011, Kovačević et al 2013a, in most of the examined media no signs of intoxication were found on shoots. In this work, only sporadic necrotic changes were found on the roots formed in medium with 10 -3 M Pb(NO 3 ) 2 , which is consistent with the results by Kovačević et al (2013a) on the same medium. However, Bojarczuk (2004) reported an inhibitory effect of the medium with pH 5.5 and 2.0 mM Pb(NO 3 ) 2 on shoot and root development of calli of hybrid aspen on regeneration medium.…”
Section: Discussionsupporting
confidence: 92%
“…Five white poplar genotypes were examined: Villafranca (Italy), L-12 (Serbia), L-80 (Serbia), LBM (Serbia), and LCM (Serbia). These genotypes have been proved suitable for biomass production, landscaping, and horticulture and suitable for in vitro testing to abiotic stresses (Kovačević et al 2013a, Vuksanović et al 2016, 2019a. According to Kovačević and Igić (2018) and Kovačević et al (2020), Villafranca, L-12 and L-80 genotypes are characterized by relatively good rooting of hardwood cuttings.…”
Section: Plant Materials and Shoot Multiplicationmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long period of time, white poplar has not been considered as a commercially important wood species. Due to climate changes and changed ecological conditions, it is becoming more interesting for breeding as a drought tolerant species (Eggens et al, 1972;Gilman and Watson, 1994;Isebrands and Richardson, 2014).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…It can solve both stochastic optimization problems and deterministic optimization problems. The injected randomness can guarantee the search less sensitive to modeling errors and escape from local minima points [261]. The common SO methods include simulated annealing (SA) [262], quantum annealing (QA) [263], random search, etc.…”
Section: Optimizationmentioning
confidence: 99%